PENGARUH PENGUNGKAPAN MODAL INTELEKTUAL PADA TINGKAT UNDERPRICING PERUSAHAAN - Prasanti, Putu Noviani Widia; Widanaputra, A A GP (E-Jurnal Akuntansi; Vol 11 No 1 (2015), 2015)
The purpose of this study was to determine the effect of intellectual capital disclosure on the level of underpricing amongst firm initial public offering and listed on the Indonesia Stock Exchange between 2009 until 2013. This research used firms that do IPO and listed on the Indonesian Stock Exchange between 2009 until 2013 as population. Sampling technique was purposive sampling method with the number of samples used in this study were 83 companies. To prove this hypothesis tested by simple linear regression analysis. This study found that intellectual capital disclosures negative and significant effect on the level of firm’s underpricing.
Keywords: IPO, Underpicing, Intellectual Capital Disclosure